COMPARISON OF INHIBITORY ACTIVITY OF KELAKAI LEAF EXTRACT AND 0.2% Chlorhexidine Gluconate AGAINST Streptococcus sanguinis ATCC® 10556™ - Fitriana Caessar Pertiwi; I Wayan Arya K. Firdaus; Isyana Erlita (Dentino : Jurnal Kedokteran Gigi, 2019)
Background: Gingivitis is an early periodontal disease that occurs due to host response and dental plaque. Streptococcus sanguinis is pioneer of dental plaque colonization in oral cavity. Gingivitis treatment use 0,2% Chlorhexidine gluconate mouthwash, but long-term use causes side effects, so an alternative herbal mouthwash which has minimal side effects is needed. Kelakai leaf ethanol extract contains antibacterial compound, such as flavonoid, alkaloid, tannin and steroid, which can be herbal-based mouthwash as an alternative of 0,2% Chlorhexidine gluconate. Purpose: It was to compare the inhibitory zone of kelakai leaf ethanol extract and 0,2% Chlorhexidine gluconate against S. sanguinis. Materials and methods: This study was true experimental research and post-test only with control group design, that used 5 treatment groups with 4 replications of kelakai leaf ethanol extract, that were 25%, 50%, 75%, 100% concentrations and 0,2% Chlorhexidine gluconate against S.sanguinis with 20 total samples. All groups incubated for 24 hours at 37oC, then it measured the diameter of inhibition zone using calliper. Result: One Way ANOVA and Post Hoc LSD tests showed significant difference between all groups after given with kelakai leaf ethanol extract and 0,2% Chlorhexidine gluconate. Kelakai leaf ethanol extract 25%, 50%, 75%, 100% concentrations and 0,2%  Chlorhexidine gluconate has an average inhibition zone, which were 9,00 mm, 11,20 mm, 13,67 mm, 16,32 mm, and 18,12 mm against S.sanguinis. Conclusion: Kelakai leaf ethanol extract 25%, 50%, 75% and 100% concentrations has antibacterial activity against S.sanguinis, but not as strong as 0,2% Chlorhexidine gluconate.